Management of Early Childhood Caries – a comparison of different approaches - J Turton, Bathsheba; Durward, Callum S (Thai Dental Public Health Journal, 2017)
Early childhood caries (ECC) is a major problem in the South East Asian (SEA) region. The management of ECC in preschool children is multi-faceted and can be challenging for the child, the dental team, and the family. There is only limited evidence for the use of specific techniques in the management of ECC. The objective of this paper is to review different treatment approaches in the management of ECC. Method: a critical review of the literature was conducted in order to examine evidence for the best techniques to manage ECC. Results: three treatment approaches were examined (1) the ‘no treatment’ approach, (2) the ‘minimally invasive dentistry’ (MID) approach, and (3) the ‘conventional’ approach. Treatment of carious lesions in the primary dentition is well-justified and results in improvements in Quality-of-Life. Recommendations for conventional treatment techniques vary widely and often require general anaesthetic to be predictable for preschool children who may have difficulty accepting treatment. The minimally invasive approach appears to be promising and centres around the use of Atraumatic Restorative Technique (ART), Arrest of Caries Treatment (ACT) with silver diamine fluoride, and the Hall crown technique. Early intervention to treat early lesions and prevent caries is very important. It can be concluded that the Minimally Invasive Dentistry (MID) approach to managing ECC appears to be the most appropriate public health approach for managing ECC in the SEA region. It would be beneficial to build more evidence around this approach in order to inform the practice of caries management in preschool children.